"If You Were Like Me, You Would Consider It Too": Suicide, Older Men, and Masculinity. (July 2018) - Apesoa-Varano, Ester Carolina; Barker, Judith C.; Hinton, Ladson
Rates of suicide are far higher for older men than for any other age or gender group. However, we know relatively little about how depressed older men think about suicide. This study addresses this gap by exploring how Latino and white non-Hispanic elderly men discuss why they would or would not contemplate suicide. Men, aged 60 and older, were screened and assessed using standard instruments for clinical depression. Those meeting criteria were invited to participate in a 1.5 to 2.5-hour in-depth interview, in either English or Spanish. Interview data come from 77 men and included men with treated and untreated depression. Men linked depression to losing their economic role, sense of productivity, and familial respect. Their narratives of suicide highlighted central tenets of hegemonic masculinity. Men from both ethnic groups asserted that "being a man" involved strength and independent choice. For some men, suicide exemplifies these ideals; for most men suicide violates them. The majority of men who felt that suicide further violated their already fragile manhood either reclaimed a decisive masculine self or embraced a caring self, especially in relation to children and family. The latter pattern raises a theoretical question regarding the symbolic boundaries of hegemonic masculinity.